The Urgency of Upgrading the Class of the Banyumas Regency DLH UPTD - Sri Huning Triastiningsih; Denok Kurniasih (International Assulta of Research and Engagement (IARE), 2025)
The purpose of this study is to analyze the urgency and feasibility of upgrading the Banyumas Regency Environmental Service UPTD from class B to class A in order to improve community services, accountability, and environmental management effectiveness. This research employs content analysis to describe and illustrate data findings in a case study of the Regional Technical Service Unit (UPTD) of the Banyumas Regency Environmental Service. The post-bureaucracy theory is used as the main theoretical framework. Data collection focuses on examining the urgency and feasibility of upgrading the UPTD from class B to class A. The analysis shows that upgrading the UPTD class at the Banyumas Regency Environmental Service is urgently needed to improve community services, guidance, empowerment, and responsiveness to environmental complaints. The transformation of the UPKP into a Waste and Environmental Management Unit (UP2LH) is justified, as it has met the requirements for a class A UPTD under Article 24 paragraph (3) letter a of the Minister of Home Affairs Regulation Number 12 of 2017. These requirements include carrying out two or more functions, covering more than one sub-district, and having a workload exceeding 10,000 effective working hours per year. The upgrade aims to enhance accountability, performance, and effectiveness in environmental management, in line with the post-bureaucracy paradigm that prioritizes public interest, quality, and value.